Analisa Variasi Busi Terhadap Performa Motor Bensin 4 Langkah - Kustiawan, Feri; , Ir.Sartono putro,MT; , Ir.Sarjito,MT,Ph.D (2016)
In the motorcycle spark plug ignition system plays an important role. Spark plug served to spark required to burn the fuel mixture with air which has been compressed. The purpose of this study was the comparison knowing torque, power, motor gasoline kbbs 4 steps resulted from standard spark plug, two legs, platinum, and iridium. This test used a motorcycle Yamaha Jupiter Z.The performance test of a motorcycle was done by dynotest (sportdyno V3.3). The test alternately for each spark plug with a variation of the engine rotation 4000-10000 rpm to 250 rpm increase in the transmission gear 3 was used to obtained the torque ratio (T), power (P), specific fuel consumption (kbbs). Peak torque was obtained at the highest iridium spark plugs, which reached 8.75 NM at 5069 rpm rotation, the highest power was resulted on iridium spark plugs and spark plug foot two that reached 8.1 Hp and 8,1Hp round 7692 rpm and 7892 rpm, specific fuel consumption best obtained on iridium spark plugs, which reached 0.078 Kg / h.Hp at 6000 rpm rotation. And prove through statistical analysis one way or one way ANOVA, with a value of F arithmetic < F table then Ho was accepted, so the results of each spark plug has a significant difference.